2007
DOI: 10.1002/cne.21357
|View full text |Cite
|
Sign up to set email alerts
|

Peptide products of the afp‐6 gene of the nematode Ascaris suum have different biological actions

Abstract: Matrix-assisted laser desorption/ionization time-of-flight and tandem time-of-flight (MALDI-TOF and MALDI-TOF/TOF) mass spectrometry were used to sequence and localize three novel, related neuropeptides in the nervous system of the nematode Ascaris suum, AMRNALVRFamide (AF21), NGAPQPFVRFamide (AF22), and SGMRNALVRFamide (AF23). The amino acid sequences were used to clone a novel neuropeptide gene (afp-6) that encodes a precursor bearing a single copy of each of the peptides. In situ hybridization and immunocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 52 publications
7
55
0
Order By: Relevance
“…These results are consistent with the fact that the majority of excitatory and inhibitory peptides were encoded on genes shown to be expressed in the C. elegans pharyngeal nervous system (23). It therefore appears that multiple FLPs are involved in feeding behavior by modulating pharyngeal activity, as supported by findings in A. suum (54, 130132). Using a modified pressure transducer, Brownlee and colleagues measured changes in intrapharyngeal pressure to monitor the contraction of the Ascaris radial pharynx muscle.…”
Section: Flp-mediated Modulation Of Nematode Physiology and Behaviorsupporting
confidence: 68%
See 2 more Smart Citations
“…These results are consistent with the fact that the majority of excitatory and inhibitory peptides were encoded on genes shown to be expressed in the C. elegans pharyngeal nervous system (23). It therefore appears that multiple FLPs are involved in feeding behavior by modulating pharyngeal activity, as supported by findings in A. suum (54, 130132). Using a modified pressure transducer, Brownlee and colleagues measured changes in intrapharyngeal pressure to monitor the contraction of the Ascaris radial pharynx muscle.…”
Section: Flp-mediated Modulation Of Nematode Physiology and Behaviorsupporting
confidence: 68%
“…In situ hybridization (ISH), which uses nucleotide probes complementary to specific gene transcripts, offers an attractive alternative to delineate flp gene expression in other nematodes that are less amenable to transgenesis than C. elegans (38, 42, 54, 75). Furthermore, as immunochemistry allows the determination of neurite morphology facilitating neuronal identification, several antibodies highly specific to certain A. suum FLPs were recently generated (42, 76).…”
Section: Localization Of Flpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Yew et al have identified a gene, which they termed afp-5 in A. suum, which encodes AF-17, which does not appear to have an equivalent in C. elegans. Recently, the gene that encodes AF-21, AF-22 and AF-23 has been cloned from A. suum and termed afp-6 (Yew et al 2007). This gene is equivalent to flp-11 of C. elegans and following on from McVeigh's nomenclature should be termed As-flp-11.…”
Section: Nematodesmentioning
confidence: 99%
“…14, 18, 19 More recently, we have used mass spectrometry (MS) to detect and then to sequence neuropeptides. 12, 13, 17, 2022 We have now extended this technique to the single cell level; mass spectrometric methods are sensitive enough both to detect and to sequence peptides from single dissected neurons. 17, 20 This approach is limited only by how successfully we can dissect single neurons.…”
Section: Introductionmentioning
confidence: 99%